Staying at Home - McCaffrey, Katherine (Anthropologica, 2021)
In the spring of 2020, the novel Coronavirus upended life in New Jersey, US, precipitating an unprecedented state lockdown of 9 million residents. The essay reflects on the author’s experience of the lockdown and her relationship to a Syrian refugee woman resettled nearby. The author identifies their shared experiences staying at home and prioritizing the collective good in the midst of a pandemic.